Origami and inattention and impulsivity among children with autism - Santamaria, Michael Luke M. (Quezon City College of Education, University of the Philippines Diliman, 2008)
The study aimed to determine whether an origami intervention program added to the typical SPED program would increase the levels of attention and impulse control of selected children with autism (CWA). The 4 respondents in the control group maintained their SPED program while the other 4 in the experimental group had an additional 20 sessions of origami intervention. Results were analyzed by obtaining the means and statistically compared using the Mann Whitney U test. It was concluded that the origami instructional manual is valid for CWA ages 4-7 years old; CWA improve their levels of attention and impulse control when provided with typical SPED program; and that there is a great potential for origami intervention among CWA in increasing their levels of attention than impulse control.
Thesis (Master of Arts in Education : Special Education)--University of the Philippines, Diliman
Keywords: Autistic children -- Education -- Philippines; Autism in children -- Philippines; Origami in education -- Philippines; Impulse control disorders -- Philippines; Special education -- Philippines